Antixenosis to Chrysodeixis includens (Lepidoptera: Noctuidae) among soybean genotypes - Schlick-Souza, Eunice Claudia; Baldin, Edson Luiz Lopes [UNESP]; Morando, Rafaela [UNESP]; Lourencao, Andre Luiz (Inst Agronomico, 2018)
The soybean looper Chrysodeixis includens is one of the main defoliating pests of soybean cultures in Brazil. This work aimed to evaluate the effect of offering different soybean genotypes to this insect to verify the occurrence of antixenosis. In a greenhouse, assays were carried out to determine the attractiveness of C. includens adults given free-choice tests. This experiment used a randomized block design with five replicates. A second experiment assessed oviposition preference using no-choice tests, employing a completely randomized design with five replicates. Seventeen soybean cultivars were used; several of these had previously been reported as carriers of resistance to more than one species of insect. In the laboratory, a morphological analysis was carried out by quantifying the number of trichomes on leaf surfaces and evaluating the color of the leaf blade of the germplasm. In the attractiveness assay, genotypes 'IAC 19', 'IAC 18', 'IAC 23', L1-1-01, PI 274453, PI 229358, PI 171451, 'IAC 100', 'IAC 24', 'IAC 17' and IAC 74-2832 were classified as repellents. In the oviposition preference experiment, PI 171451, PI 274453, 'IAC 18', L1-1-01 and 'IAC 23' showed the fewest eggs. The high density of trichomes presented by the genotypes PI 227687 and PI 274453 stand out as a possible C. includens resistance factor. The genotype L1-1-01 presented intermediate luminosity (L*) and more intense green (a*) and yellow (b*) colors compared to other genotypes. There was no correlation between oviposition and trichome density or leaf coloration.
Keywords: Glycine max; soybean looper; host plant resistance to insects; non-preference